BASAL-BOLUS INSULIN THERAPY VS SLIDING SCALE INSULIN IN THE MANAGEMENT OF TYPE 2 DIABETES PATIENTS IN A CORONARY CARE UNIT - Khan, Qurban; Siddique, Abdul Hameed; Malik, Sadia; Janjua, Hafsa; Khan, Muhammad] Qaiser; Aziz, Sohail; Naqvi, Shahab; Majeed, Syed Muhammad Imran (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the efficacy and safety of a basal bolus insulin with that of sliding scale. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at AFIC-NIHD Rawalpindi from Oct to Dec 2014. Methods: We conducted a quasi experimental study to compare the efficacy and safety of a basal-bolus insulin regimen with that of sliding-scale insulin (SSI) in patients with type 2 diabetes. A total of 89 patients received either a basal-bolus regimen comprising both regular and NPH insulin (n=46) or a standard SSI protocol (n=43). NPH insulin was given twice daily and regular insulin before meals. The starting dose of insulin for insulin-naïve patients who received the basal-bolus regimen was 0.3 units/kg/day in underweight patients, 0.4 units/kg/day in normal weight patients, 0.5 units/kg/day in overweight patients and 0.6 units/kg/day in obese patients. Patients who had been on insulin therapy previously received the same total daily dosage (TDD) of insulin that they were previously being treated with. In the SSI regime, regular insulin was given three times per day for blood glucose >140 mg/dl before meals. Results: The mean admission blood glucose was 246 mg/dl in the basal-bolus group and 234 mg/dl in the SSI group. A mean blood glucose target of <180 mg/dl was achieved in 63% of patients in the basal-bolus group and in 26% of those in the SSI group. The difference in mean daily blood glucose between groups ranged from 34mg/dl to 61mg/dl with an overall difference of 37 mg/d (p=0.005). Despite increasing insulin doses, 33% of patients treated with SSI had mean blood glucose > 240 mg/dl. Hypoglycemia occurred in 13% of patients in the basal-bolus group and 5% of the SSI group. Conclusion: Treatment with basal-bolus insulin resulted in significant improvement in glycemic control compared with that achieved with the use of SSI alone, although the incidence of hypoglycemia was greater. Our study indicates that a basal-bolus insulin regimen is preferred over SSI in the management of hospitalized patients with type 2 diabetes admitted to a coronary care unit.